On Being Consumed: The Martyred Body as a Site of Divine—Human Encounter in the Letters of Ignatius of Antioch - Peter-Ben Smit (Religions, 2020)
The manner in which humans and the divine are brought into communion with each other, a key aspect of many religious traditions, is frequently, if not always, material (or sacramental) in character. Meals and food play an important role in this; such meals can include the consumption of the deity (theophagy), as well as the consumption of the human being by the deity. This paper takes its cue from the discussion of constructions of divine–human communion and explores this subject in the letters of Ignatius of Antioch (early second century CE). It shows how in the literary heritage of this bishop, the body as the physical site of martyrdom is of key importance, in particular due to its consumption in the Roman arena. This martyrdom is the way in which Ignatius hopes to enter into perfect communion with the divine. The body thus becomes, in its annihilation, the instrument through which divine–human communion is established. As this all relates to a case of martyrdom, Ignatius’ ideas about the body are also subversive in character: the punishment of his body is, through his theological imagination, transformed into a means of achieving Ignatius’ goal in life: attaining to God.